STUDI KOMPARASI VOLUME PENJUALAN DAN PENDAPATAN PRODUK SELIS (SEPEDA LISTRIK) DI SHOPEE & TOKOPEDIA - Aldi Akbar; Ulfa Azizah (Institut Pendidikan Tapanuli Selatan, 2024)
This study compares the sales volume and revenue of selis products at Shopee and Tokopedia. This study aims to analyze the comparison of sales volume and revenue of selis products at Shopee and Tokopedia. This research uses quantitative methods with a descriptive approach. The results showed that Shopee has a higher sales volume of selis products than Tokopedia. This is due to Shopee having a larger number of users than Tokopedia. Shopee recorded higher sales volume (37 units) than Tokopedia (15 units) in 2023, driven by a larger number of users. Nonetheless, the average revenue of selis products in Tokopedia reached Rp. 151,983,166.67, while in Shopee it reached Rp. 161,325,000.00 in the same year, due to more discounts in Shopee. With increased buying interest, Shopee and Tokopedia stand out as potential e-commerce platforms for marketing selis products in Indonesia.